Coexistence of papillary renal cell carcinoma and gastrointestinal stromal tumor in a case - Berkan REŞORLU; Sümer BALTACI; Mustafa REŞORLU; Duygu KANKAYA; Berna SAVAŞ (Turkish Journal of Gastroenterology, 2019)
-